2014
DOI: 10.1590/s0100-29452014000500030
|View full text |Cite
|
Sign up to set email alerts
|

Atividade antioxidante, citotóxica e antimicrobiana de Annona vepretorum Mart. (Annonaceae)

Abstract: Annona vepretorum Mart. é uma espécie endêmica do bioma Caatinga, conhecida no Nordeste do Brasil como "araticum". Neste trabalho, o conteúdo de fenóis totais foi determinado pelo método de Folin-Ciocalteu. O teor de flavonoides totais também foi medido. A atividade antioxidante dos extratos foi analisada pelos métodos do sequestro do radical DPPH e inibição da auto-oxidação do β-caroteno, e comparada com o ácido ascórbico, BHA e BHT, utilizados como compostos de referência. A análise de citotoxidade foi reali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
2
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 10 publications
1
10
2
2
Order By: Relevance
“…Phytochemical analysis showed the presence of flavonoids, except in crude hexane extract (Av-HexC), confirming previous studies with A. vepretorum [15]. A large number of biological activities have been attributed to these compounds, including anticancer activity [19].…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Phytochemical analysis showed the presence of flavonoids, except in crude hexane extract (Av-HexC), confirming previous studies with A. vepretorum [15]. A large number of biological activities have been attributed to these compounds, including anticancer activity [19].…”
Section: Discussionsupporting
confidence: 87%
“…In addition, research has shown that the ethanol extract has anti-inflammatory and antinociceptive activity, which is related probably with the activation of opioid receptors and inhibition of release of mediators of the inflammatory process [14]. Antioxidant, cytotoxic and antimicrobial activities have also been reported for this plant [15].…”
Section: Introductionmentioning
confidence: 95%
“…SF32-33 had a dose- and time-dependent effect on P. aeruginosa ATCC 27853. Indeed, these effects were observed as soon as 6 h post-incubation of SF32-33 and lasted for 24 h. Although antibacterial activity has been attributed to fractions obtained from other plants of the Annona genus ( A. vepretorum and A. hypoglauca ), their MIC and MBC were much higher (≤100 mg/ml; Almeida et al, 2014; Rinaldi et al, 2016) in comparison to those observed for the EAF of A. glabra in our study (≤16 μg/ml).…”
Section: Discussioncontrasting
confidence: 70%
“…The hexane and chloroform fractions obtained from Annona vepretorum leaves display antimicrobial activity against Escherichia coli, Klebsiella pneumoniae , and Staphylococcus aureus (Almeida et al, 2014). Additionally, Rinaldi and collaborators showed that the methanol, dichloromethane, and ethyl acetate fractions (EAFs) obtained from Annona hypoglauca stems inhibited the growth of Staphylococcus aureus and Enterococcus faecalis (Rinaldi et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…There is no consensus on the acceptable level of inhibition for natural products when compared with antibiotics standards. Some authors consider only results similar to antibiotics, while others consider with good potential even those with lower levels of inhibitions (Almeida et al, 2014).…”
Section: Discussionmentioning
confidence: 99%